Políticas públicas de prevenção e enfrentamento à violência contra a mulher no município de Marau/RS : uma análise sob a perspectiva da redistribuição, do reconhecimento e da representação - Rodrigues, Cristiane Terezinha (2025)
Domestic violence against women, rooted in the patriarchal structure, remains present in social relations and is currently considered a public issue. In this context, it is the responsibility of the public authorities to act through the formulation and implementation of public policies aimed at preventing and supporting women in situations of violence. Given this scenario, the present research, affiliated with the Research Line "Social Relations and Dimensions of Power" and the Concentration Area "New Paradigms of Law" of the Graduate Program in Law at UPF, aims to analyze public policies for the prevention and combat of violence against women in the municipality of Marau/RS, investigating their contribution to the realization of social justice based on the theoretical pillars of redistribution, recognition, and representation proposed by Nancy Fraser. For the development of this study, both deductive and inductive research approaches were used. The study adopts bibliographic and documental research as an investigative procedure, utilizing books, scientific articles, legislation, international treaties, institutional documents, as well as documents from the municipal government of Marau as its analytical basis. The results indicate that the municipality, through its network for the prevention and combat of violence against women, develops innovative actions that address both the direct fight against violence and the promotion of awareness and cultural transformation, contributing to the realization of women's rights. However, the research identifies the need to improve data collection and monitoring to enable the verification of the effectiveness and efficiency of these actions, as well as to contribute to the enhancement of public policies. In conclusion, the public policies developed in the municipality of Marau reflect a significant effort in promoting social justice and to comply with national and international guidelines on the subject, despite the challenges that remain. Therefore, the continuity and strengthening of these policies are essential to ensuring the enforcement of women's rights and the mitigation of gender-based violence, reinforcing the municipality's commitment to equity and social transformation.